Big data and more at the 2017 Sports Analytics Conference, Australia - Allen, S. V.; Hopkins, W. G. (Sportscience, 2017)
This one-day conference in Melbourne on August 4 is an annual event that began in Australia just a few years ago and now extends to Asia and Europe. Check out the series website for any forthcoming conference near you, and don't miss it! The website does not name organizing or founding personnel, but it appears to be an initiative of the Vumero Institute, which positions itself as "the world's education company for finance, technology, and data-driven industries." It's hype, of course, but they certainly promoted a winner on this occasion.